The validation of a paddle power meter for slalom kayaking - Macdermid, P. W.; Fink, P. W. (Sports Medicine International Open, 2017)
The ability to quantify power within the sport of slalom kayaking would provide coaches and athletes objective data to monitor performance. This study determined the validity of a kayak paddle power meter and subsequent relationship between work rate and stroke kinetics. One participant completed multiple trials of a flat-water, straight-line sprint and a sequence of slalom gates at numerous intensities to attain the velocity:power relationship. Laboratory results identified the kayak paddles` strain gauges were valid and reliable, and field tests presented a cubic relationship for power as a function of velocity in the straight-line sprint (R2=0.982) and the slalom-specific test (R2=0.993). Further analysis of stroke kinetics identified velocity of hand movement at individual peak force capability to be critical in the highest work rates achieved for both slalom and flat-water sprinting. It was concluded that the kayak paddle power meter tested is a valid means of recording work rate and stroke kinetics during kayaking in the field.